1987
DOI: 10.1287/mnsc.33.9.1137
|View full text |Cite
|
Sign up to set email alerts
|

Freezing the Master Production Schedule Under Rolling Planning Horizons

Abstract: The stability of the Master Production Schedule (MPS) is a critical issue in managing production operations with a Material Requirements Planning System. One method of achieving stability is to freeze some portion or all of the MPS. While freezing the MPS can limit the number of schedule changes, it can also produce an increase in production and inventory costs. This paper examines three decision variables in freezing the MPS: the freezing method, the freeze interval length, and the planning horizon length. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
5

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 18 publications
0
64
1
5
Order By: Relevance
“…Blackburn et al (1986Blackburn et al ( , 1987 investigated five different strategies for reducing MRP nervousness and found freezing the MPS to be among the most effective strategies. Sridharan et al (1987Sridharan et al ( , 1988 developed a method to measure schedule instability and studied the impact of MPS freezing upon inventory costs and schedule instability in single-level MPS systems under deterministic demand. Sridharan and Berry (1990b) presented a framework for designing MPS freezing methods under deterministic demand.…”
Section: Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Blackburn et al (1986Blackburn et al ( , 1987 investigated five different strategies for reducing MRP nervousness and found freezing the MPS to be among the most effective strategies. Sridharan et al (1987Sridharan et al ( , 1988 developed a method to measure schedule instability and studied the impact of MPS freezing upon inventory costs and schedule instability in single-level MPS systems under deterministic demand. Sridharan and Berry (1990b) presented a framework for designing MPS freezing methods under deterministic demand.…”
Section: Related Researchmentioning
confidence: 99%
“…Sridharan and Berry (1990a), LaForge (1990, 1994), Lin and Krajewski (1992) extended the studies by Sridharan et al (1987Sridharan et al ( , 1988 from the case of deterministic demand to the case of demand uncertainty by introducing forecasting errors into the system. Lee (1993, 1996) and Zhao and Lam (1997) extended the studies by Sridharan et al (1987Sridharan et al ( , 1988) from single-level systems to multilevel MRP systems and found that some findings in single-level systems cannot be generalised to multi-level systems. Zhao and Lee (1993) investigated the impact of forecasting errors on the performance of the MPS freezing parameters by simulating the forecasting process as well as the master production scheduling and MRP processes in multi-level MRP systems.…”
Section: Related Researchmentioning
confidence: 99%
See 3 more Smart Citations